Influence of adherence with guideline-driven recommendations on survival in women operated for breast cancer: Real-life evidence from Italy - Giovanni Corrao (Breast, 2020)
Background: A set of indicators to assess the quality of care for women operated for breast cancer was developed by an expert working group of the Italian Health Ministry in order to compare the Italian regions. A study to validate these indicators through their relationship with survival was carried out. Methods: The 16,753 women who were residents in three Italian regions (Lombardy, Emilia-Romagna and Lazio) and hospitalized for breast cancer surgery during 2011 entered the cohort and were followed until 2016. Adherence to selected recommendations (i.e., surgery timeliness, medical therapy timeliness, appropriateness of complementary radiotherapy and mammographic follow-up) was assessed. Multivariable proportional hazards models were fitted to estimate hazard ratios for the association between adherence with recommendations and the risk of all-cause mortality. Results: Adherence to recommendations was 53% for medical therapy timeliness, 73% for appropriateness of mammographic follow-up, 74% for surgery timeliness and 82% for appropriateness of complementary radiotherapy. Risk reductions of 26%, 62% and 56% were observed for adherence to recommendations on medical therapy timeliness, appropriateness of complementary radiotherapy and mammographic follow-up, respectively. There was no evidence that mortality was affected by surgery timeliness. Conclusions: Clinical benefits are expected from improvements in adherence to the considered recommendations. Close control of women operated for breast cancer through medical care timeliness and appropriateness of radiotherapy and mammographic monitoring must be considered the cornerstone of national guidance, national audits, and quality improvement incentive schemes.